2004
DOI: 10.1111/j.1365-2222.2004.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy and non‐allergic food hypersensitivity in children and adolescents

Abstract: The perception of food-related symptoms is common among children and adolescents from the general population. Self-reports could be confirmed in around one out of 10 individuals, still resulting in 4.2% of proven clinical symptoms. However, most reactions were mild and mainly because of pollen-associated FA, while NAFH reactions were less common. Severe IgE-mediated FA was observed in individuals with pre-existing atopic disease, who should be fully investigated for clinically relevant FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
5
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(207 citation statements)
references
References 44 publications
9
178
5
15
Order By: Relevance
“…In our study, chocolate allergy (21.2%) was in the second order. While the most commonly reported food was fruit in the study performed by Roerh and Osterbella (14,15), it was egg (25.3%) in our study. Egg was in the 5 th order with a rate of 6.6% in the study of Roerh (14) and in the 3rd order with a rate of 13.3% in the study of Osterbella (15).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our study, chocolate allergy (21.2%) was in the second order. While the most commonly reported food was fruit in the study performed by Roerh and Osterbella (14,15), it was egg (25.3%) in our study. Egg was in the 5 th order with a rate of 6.6% in the study of Roerh (14) and in the 3rd order with a rate of 13.3% in the study of Osterbella (15).…”
Section: Discussioncontrasting
confidence: 52%
“…McBride et al reported the prevalence of FA reported by parents to be 5-30% in the comprehensive EuroPrevall birth cohort study conducted in 9 European countries which covered the years of 2005-2010 (4). In other studies on the prevalence of food allergy which used a questionnaire, Orhan et al (8) reported the prevalence to be 5.7% in 3500 school children aged between 6 and 9 in Eastern Black Sea region, Roehr et al (14) reported the prevalence to be 31.4% in 2354 children aged between 0 and 17 years in Germany and Osterballe et al (15) reported the prevalence to be 16.6% in individuals aged between 0 and 22 years. In these three studies, the prevalence was found to be 0.8%, 3.5% and 3.3%, respectivley after skin prick test and DBPCCT were performed (16).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-third of self-reported FHS have been confirmed by oral challenges in other studies (3)(4)(5), varying with age, study design, and food type (7,23,24,28,29). We found that 31% (20 of 65) of all self-reported FHS during the 6-year period could be confirmed by challenge.…”
Section: Discrepancy Between Self-reported and Confirmed Fhssupporting
confidence: 58%
“…It may cause reactions, such as urticaria, angioedema, and anaphylaxis, due to immunoglobulin E (IgE)-induced type 1 reaction. In addition, reactions, such as atopic dermatitis and eosinophilic gastroenteropathy, may occur in mixed and nonIgE-mediated forms (1)(2)(3)(4). Ovomucoid (Gad d 1), ovalbumin (Gad d 2), ovotransferrin (Gad d 3), lysozyme (Gad d 4), and ovomucin, which are the five major proteins found in egg white, cause more allergies (2).…”
Section: Introductionmentioning
confidence: 99%
“…Egg allergies are diagnosed with a careful patient history (clinical history) and a skin prick test and specific IgEs that support it. A double-blind, placebo-controlled oral food provocation test is still the gold standard for the diagnosis of food allergies (3)(4)(5). Despite the limited number of studies in the literature, measles, MMR, and chickenpox vaccinations are considered safe in children with egg allergy although disputes continue.…”
Section: Introductionmentioning
confidence: 99%